2016
DOI: 10.1089/ars.2015.6421
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemia Engages the RhoA Kinase Pathway to Impair Cardiac Function By Altering Cytoskeleton, Mitochondrial Fission, and Autophagy

Abstract: Fasudil prevented LPS-induced heart oxidative stress, abnormal F-actin distribution, and oxidative phosphorylation, which concur to improve cardiac contractile and bioenergetic function. We suggest that fasudil may represent a valuable therapy for patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 42 publications
7
58
0
Order By: Relevance
“…A new published study showed that myocardial aging is a T-cell-mediated phenomenon that heart-directed immune responses may spontaneously arise in the elderly [23]. Improvement of LPS-induced mitochondrial dysfunction by fasudil was attributed to inhibition of ROCK-dependent Drp1 phosphorylation and activation of autophagic processes [24]. Overall our data indicate the relationship between AMPK and autophagy response to LPS treatment in heart dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…A new published study showed that myocardial aging is a T-cell-mediated phenomenon that heart-directed immune responses may spontaneously arise in the elderly [23]. Improvement of LPS-induced mitochondrial dysfunction by fasudil was attributed to inhibition of ROCK-dependent Drp1 phosphorylation and activation of autophagic processes [24]. Overall our data indicate the relationship between AMPK and autophagy response to LPS treatment in heart dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…A related physiological process critical in energy maintenance that is activated by stress conditions, including infection, is autophagy. Recent studies highlight the contribution of proper autophagy regulation for cardiac function [41,42]. As we report here, pre-treatment with metformin protected the heart from the LPS-induced autophagy dysregulation, an additional indication for the effects of metformin on cardiac metabolism.…”
Section: Discussionsupporting
confidence: 65%
“…Herein, the well-characterized NR8383 macrophages were used to investigate the effects of the HO-1/CO system on the levels of Fis1 and LPS-induced oxidative injury of cells and attempted to elucidate the possible mechanism of action. A number of studies indicated that abnormal mitochondrial fission was a determinant in the pathogenesis of sepsis (2,28,29). Fis1, a small molecule uniformly located in the mitochondrial outer membrane, was necessary for mitochondrial fission and removal of dysfunctional mitochondria (30,31).…”
Section: Discussionmentioning
confidence: 99%